1981
DOI: 10.1111/j.1524-4725.1981.tb00191.x
|View full text |Cite
|
Sign up to set email alerts
|

Necroscopic Findings of Pleomorphic, Variably Acid‐Fast Bacteria in a Fatal Case of Kaposi's Sarcoma

Abstract: Bacteriologic findings in a fatal case of Kaposi's sarcoma are recounted and the issue of an infectious cause for Kaposi's sarcoma is explored.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

1984
1984
2014
2014

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 22 publications
1
3
0
Order By: Relevance
“…This study strongly suggests that African eosinophilic bodies are similar in nature to intracellular and extracellular coccoid forms and larger Russell bodies that Cantwell 11–16 and others have observed in vivo in a variety of disease states, including cancer, AIDS, lymphoproliferative diseases, and certain collagen diseases. Cantwell has suggested that these variably acid‐fast coccoid and pleomorphic forms may represent cell wall‐deficient bacteria in vivo 11–16 …”
Section: Commentssupporting
confidence: 74%
See 1 more Smart Citation
“…This study strongly suggests that African eosinophilic bodies are similar in nature to intracellular and extracellular coccoid forms and larger Russell bodies that Cantwell 11–16 and others have observed in vivo in a variety of disease states, including cancer, AIDS, lymphoproliferative diseases, and certain collagen diseases. Cantwell has suggested that these variably acid‐fast coccoid and pleomorphic forms may represent cell wall‐deficient bacteria in vivo 11–16 …”
Section: Commentssupporting
confidence: 74%
“…The possible role of variably acid‐fast bacteria as opportunistic agents in KS, 11–12,14–16 as proposed by Cantwell, is highly controversial. However, it is important that this theory be evaluated and judged with some knowledge of the various morphologic forms, as well as the clinical, bacteriologic, and immunologic peculiarities, that have been ascribed to cell wall‐deficient bacteria 16 .…”
Section: Commentsmentioning
confidence: 99%
“…Cantwell pointed out that there was a very close link between bacteria and cancer as well as AIDS [25][26][27][28]. This interest in investigating bacteria and mycoplasma in this disease was also supported by Montagnier's finding, confirmed by Shyh-Ching Lo, that mycoplasma is a very important "co-factor" which accelerates the progression of HIV infection in AIDS patients [29,30].…”
Section: Some Groundbreaking Findings Made By Livingston Broxmeyer Andmentioning
confidence: 99%
“…And finally, Cantwell and Broxmeyer pointed out that there is a very close relationship between bacteria and cancer, resp. AIDS (Cantwell, 1983(Cantwell, , 1993Broxmeyer & Cantwell, 2008).…”
Section: Introductionmentioning
confidence: 99%